2023
DOI: 10.1093/femsec/fiad002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of prebiotic effects of four oligosaccharides usingin vitrogut model: digestibility, microbiome, and metabolome changes

Abstract: Fructooligosaccharides (FOS), Ad-fructooligosaccharides (Ad-FOS), resistant maltodextrin (RMD), and maltooligosaccharides (MOS) are commercially available prebiotic oligosaccharides. In this study, the effects of prebiotics on the human gut microbial ecosystem were evaluated using an in vitro gut model. FOS and Ad-FOS showed tolerance to digestion, whereas RMD and MOS showed moderate digestion by digestive enzymes. In in vitro fecal fermentation, Bifidobacterium spp. increased in the following order: FOS, Ad-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Various strains of L. plantarum and L. fermentum have been documented to utilize scFOS and produce metabolites. [13,14] L. rhamnosus GG is a non-FOS fermenting strain and hence we do not get any appreciable growth or metabolite production in presence of scFOS. [15][16][17][18].…”
Section: Discussionmentioning
confidence: 78%
“…Various strains of L. plantarum and L. fermentum have been documented to utilize scFOS and produce metabolites. [13,14] L. rhamnosus GG is a non-FOS fermenting strain and hence we do not get any appreciable growth or metabolite production in presence of scFOS. [15][16][17][18].…”
Section: Discussionmentioning
confidence: 78%
“…A one-way analysis of variance (ANOVA) followed by Tukey's test (for normally distributed data) was employed to compare significant differences in metabolite changes between the before and after fermentation with different starter strains. All p-values were corrected using the FDR correction method [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, indigestible, fermentable, resistant maltodextrin was proven to have prebiotic functions, as consumption of RMD increased gut microbiota richness, particularly the Bifidobacteria count, and short chain fatty acid (SCFA) production [40][41][42]. Recent reports revealed that when compared to FOS, RDM intake was more efficient in the production of acetate, butyrate, propionate, and total SCFA, as well as lower in trimethylamine synthesis [13,43]. However, evidence was lacking about the impact of RMD on disease prevention, including intestinal epithelium and kidney health.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies disclosed the usefulness of other prebiotics in modifying gut microbiota and modulating gut and other systemic diseases. Chitosan, as a non-plant derived prebiotic, was used to treat bowel inflammation and metabolic syndrome [11,12], and maltodextrin, a starch commonly used as a placebo, was lately reported to contain prebiotic properties [13].…”
Section: Introductionmentioning
confidence: 99%